ORGANIZATIONAL ISSUES OF SOCIO-PSYCHOLOGICAL SERVICE DELIVERY IN HIGHER EDUCATION - Omonova Sevara Ma’mirjonovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article is devoted to the organization of socio-psychological services in higher education. The article discusses the scientific and methodological foundations of the psychological service, its organizational issues, ensuring the effectiveness of educational activities in universities, comprehensive support for students, psychological support for students in the development of professional knowledge and skills, and creating a positive psychological climate in the educational process. Also, issues such as learning and overcoming problems, as well as issues related to mastery using advanced psychological methods, are widely covered.